Anodic Mechanism of 1, 1′‐Bis(diphenylphosphino)ferrocenedicarbonylnickel Determined by Low‐Temperature Spectroelectrochemistry. Issue 19 (9th May 2019) - Ringenberg, Mark R.; Döttinger, Florian
Abstract : [Ni(CO)2 (dppf)] [1 ] dppf = 1, 1′‐bis(diphenylphosphino)ferrocene was made by reductive carbonylation of [NiCl2 (dppf)] with [Fe(CO)5 ], similar to our recent report in Organometallics, 2019, 38, 586–592. Complex [1 ] showed two oxidation waves in the cyclic voltammogram. UV/Vis‐NIR spectroelectrochemistry (SEC) and IR SEC at –30 °C as well as computational support by means of DFT was used to assign the oxidation state of both metal atoms after oxidation. The monocation [1 ] + showed a strong NIR absorption band which was described as an IVCT [Ni I →Fe II ] and inverse IVCT (iIVCT) or hole transfer [Fe II →Ni I ] based on time dependence DFT (TD‐DFT). The IR SEC spectrum of [1 ] + showed multiple bands associated with two similar configurations, one which had the spin delocalized over both metal atoms and a second configuration where the spin is primarily Ni localized. The second oxidation to [1 ] 2+ occurred at the Ni atom and resulted in release of a CO ligand followed by the formation of dimeric complex determined by low temperature IR SEC. Abstract : A 1, 1′‐bis(diphenylphosphino)ferrocenedicarbonylnickel complex was synthesized by reductive carbonylation of [NiCl2 (dppf)] with [Fe(CO)5 ] and its electrochemical behavior was investigated.